PENGEMBANGAN GAME EDUKASI MATH MAZE BERBASIS MULTIMEDIA INTERAKTIF KONVERSI PECAHAN DESIMAL KELAS IV - Agustina Elisa; Kenti Yuliana (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
The objectives are: To develop a Math Maze educational game application for Decimal Fraction Conversion material for grade IV students, to determine the feasibility of the Math Maze educational game application for Decimal Fraction Conversion material for grade IV students. Research and development results: The process of developing learning media is carried out in 10 stages of development, namely: Potentials and problems, data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision, and production. The feasibility level of learning media is reviewed based on the validation of experts and the results of trials to students. the average assessment of the eligibility of material experts is 4.61 with the